Perbedaan Self-regulated Learning Siswa Sekolah Menengah Kejuruan berdasarkan Jenis Kelamin - Saputra, Wahyu Nanda Eka; Alhadi, Said; Supriyanto, Agus; Wiretna, Claudy Desya; Baqiyatussolihat, Babay (Jurnal Kajian Bimbingan dan Konseling, 2018)
The purpose of this study was to identify the differences in self-regulated learning of male and female students in Sekolah Menengah Kejuruan Muhammadiyah in Yogyakarta, Special Region of Yogyakarta, Indonesia. This quantitative study using comparative method involving 414 students consisting of 226 male students and 188 female students as sample. The sample selection used Stratified Random Sampling technique. The instrument was the Self-regulated Learning Scale. To identify the differences in self-regulated learning of male and female students, Independent Sample Test were used. The results showed that there were significant differences between self-regulated learning of male and female students at Sekolah Menengah Kejuruan Muhammadiyah in Yogyakarta. And, self-regulated learning of female student was higher than male students. The particular study recommended the need for counseling services to improve student self-regulated learning.